The paper kingdom (Random House, 2020)
Accompanying his parents to their night-shift jobs as office cleaners, young Daniel reluctantly joins in as they use their imaginations to transform the deserted building into a magnificent paper kingdom where he might one day rule.

I am thankful: a positive power story (Positive power, ,, 2017)
Throughout a Thanksgiving Day filled with family and fun, a child finds opportunities to be thankful.

I am helpful: a positive power story (Positive power, ,, 2018)
A little girl thought that having a baby sister would be fun. But with a different daily routine at home, and her parents constantly distracted by the family's newest member, the little girl has a lot to adjust to. However, by helping her parents, and taking on special jobs, like singing to the baby, she learns that being a big sister comes with big rewards (though a little spit-up too).